Analisis Faktor-Faktor Penetapan Harga Jual UMKM Baju Tenunku by Aldi Wibowo - Dhae, Didaktus Febrino; Oktariyana, Made Denny; Tomasowa, Thobias E. D. (Jurnal Inovasi Akuntansi (JIA), 2025)
This research aims to analyze the internal and external factors that influence pricing decisions at the MSME Baju Tenunku by Aldi Wibowo. This study uses a descriptive approach. Quantitative descriptive analysis was conducted by calculating Cost-Based Pricing for eight product types, while qualitative methods were used to identify other determining factors. The results show that Cost-Based Pricing is the primary method applied. Dominant internal factors include the production cost structure (raw materials, labor, overhead), design complexity, and the cultural value embedded in the woven fabrics. Significant external factors are market trends, consumer demand, and competitor pricing. It was found that this MSME applies a varied markup ranging from 30% to 50%, adjusted based on difficulty level, aesthetic value, and market segmentation. In conclusion, Baju Tenunku does not purely use one method but rather integrates a cost-based pricing approach with value-based pricing. The final selling price reflects not only production costs and profit margins but also the cultural value, exclusivity, and local identity of the product, thereby creating a competitive and sustainable pricing strategy.